2020
DOI: 10.3390/molecules25051166
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Capsule-Brewed Espresso Coffee Aroma from the Most Widespread Italian Brands by HS-SPME/GC-MS

Abstract: Coffee capsules market is on the rise as it allows access to a wide selection of coffee, differing in taste and brand. However, few data about the chemical characterization of the capsule-brewed coffee aroma are available. In this work, an untargeted approach using headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography–mass spectrometry (GC-MS) and combined to chemometrics was performed to study and compare aroma profile from 65 capsule-brewed espresso coffees (ECs) commercialized by fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 30 publications
(76 reference statements)
4
36
0
Order By: Relevance
“…There were non-significant differences ( p > 0.05) between samples for compounds C2, C5, C7, C8, 12, C27, and C31; all other compounds presented significant differences ( p < 0.05) between the coffee samples. In Table 3 , it can be observed that most of the volatile compounds are associated with coffee, cocoa, and nutty aromas, which have also been reported in other published studies, some of these are furans such as 2,5-dimethylfuran (C2), 2-methoxymethyl furan (C8), 2-acetyl furan (C12), 2,2-methylenebisfuran (C31), furfuryl propionate (C32); pyrazines such as 2-methylpyrazine (C7), 2-ethylpyrazine (C13), coffee pyrazine (C20), and nutty pyrazine (C36), among others [ 12 , 13 , 56 ]. The most abundant compound based on the peak area for all samples was furfuryl acetate (C18), which has been related to fruit, banana, and ethereal aromas ( Table S1 ); other authors have also found this compound in arabica [ 57 ], and robusta [ 58 ] coffees and they have associated this compound also with a floral aroma.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…There were non-significant differences ( p > 0.05) between samples for compounds C2, C5, C7, C8, 12, C27, and C31; all other compounds presented significant differences ( p < 0.05) between the coffee samples. In Table 3 , it can be observed that most of the volatile compounds are associated with coffee, cocoa, and nutty aromas, which have also been reported in other published studies, some of these are furans such as 2,5-dimethylfuran (C2), 2-methoxymethyl furan (C8), 2-acetyl furan (C12), 2,2-methylenebisfuran (C31), furfuryl propionate (C32); pyrazines such as 2-methylpyrazine (C7), 2-ethylpyrazine (C13), coffee pyrazine (C20), and nutty pyrazine (C36), among others [ 12 , 13 , 56 ]. The most abundant compound based on the peak area for all samples was furfuryl acetate (C18), which has been related to fruit, banana, and ethereal aromas ( Table S1 ); other authors have also found this compound in arabica [ 57 ], and robusta [ 58 ] coffees and they have associated this compound also with a floral aroma.…”
Section: Resultssupporting
confidence: 66%
“…To ensure that the final products (brewed coffee) will be acceptable by consumers, different techniques are used to assess their quality traits. Traditional methods to assess aromas in coffee consist of either instrumental techniques using gas-chromatography/mass-spectroscopy (GC/MS) [ 12 , 13 ], or most commonly through sensory analysis using descriptive sensory panels [ 14 ] and methods such as quantitative descriptive analysis (QDA ® ), or expert panels. The latter tend to be less reliable as sensory panels are often subjected to more biases, such as the habituation error [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are classified by chemical classes into pyrazines, furans, aldehydes, ketones, and pyrroles. These compounds are present together with phenols, hydrocarbons, acids and anhydrides, esters, alcohols, sulfur compounds, and others [37,38]. Quantitatively, the main two chemical classes in coffee are furans and pyrazines, while qualitatively, sulfur-containing compounds together with pyrazines are considered the most significant to coffee flavor [25,39].…”
Section: Aroma Profile Of Espresso Coffee (Ec)mentioning
confidence: 99%
“…These compounds exhibit variable changes in concentration and sensory potency, which explains why different coffee types may have such unique and specific flavors [46]. It was reported that espresso coffee (EC) contains volatile components belonging to different chemical classes such as furans, pyrazines, aldehydes, ketones, phenolic, and sulfur compounds [37,[47][48][49].…”
Section: Aroma Profile Of Espresso Coffee (Ec)mentioning
confidence: 99%
See 1 more Smart Citation